2007
DOI: 10.1111/j.1651-2227.2007.00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection among children with gastrointestinal symptoms: a high prevalence of infection among patients with reflux oesophagitis

Abstract: The prevalence of H.pylori was significantly higher among patients with reflux oesophagitis compared to patients with hyperaemic gastropathy alone. Adjusting for age the prevalence of H.pylori infection was not higher among symptomatic children compared to asymptomatic children of the same age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 20 publications
2
21
0
1
Order By: Relevance
“…Similar to our findings of an increased prevalence of RE in H. pylori positive patients, Daugule et al (24) showed that the prevalence of H. pylori was significantly higher among children with RE than in children with hyperemic gastropathy. We also found that H. pylori infection was more closely associated with RE in younger children (0–10 years) than in older children (> 10 years), although this may be related to an age specific distribution of H. pylori gastritis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar to our findings of an increased prevalence of RE in H. pylori positive patients, Daugule et al (24) showed that the prevalence of H. pylori was significantly higher among children with RE than in children with hyperemic gastropathy. We also found that H. pylori infection was more closely associated with RE in younger children (0–10 years) than in older children (> 10 years), although this may be related to an age specific distribution of H. pylori gastritis.…”
Section: Discussionsupporting
confidence: 92%
“…There are limited data regarding the relationship between H. pylori infection and GERD in the pediatric population (2124). Levine et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of harboring H. pylori Ag was increased with age above 5 years who having burning sensation and unprotected water source. A large body of evidence shows that the prevalence of H. pylori was significantly higher among children with reflux oesophagitis than in children with hyperemic gastropathy [31] . However, we could not find any significant difference between H. pylori positive and negative cases in the incidence of nausea, and vomiting [32] , or diarrhea [33] .…”
Section: Patientsmentioning
confidence: 99%
“…Baltijos regione (Estijoje, Latvijoje, Lietuvoje) H. pylori paplitimas vaikų populiacijoje svyruoja nuo 18 iki 55 proc. [7,8]. Lietuvoje 1999 m. paplitimas tarp tirtų 10-14 metų vaikų sudarė 25-55 proc., 2012 m. tarp medicinos studentų paplitimas sudarė 25 proc.…”
Section: Diskusijaunclassified